Penetapan Kadar Flavonoid Ekstrak Daun Binahong (Basella rubra L.) Dengan Tingkat Fraksi Menggunakan Metode Spektrofotometri UV–VIS - Ningsih, Gusria Surya; Rohama, Rohama; Hastika, Febby Yulika; Nastiti, Kunti (LPPM Institut Pendidikan Nusantara Global, 2025)
Degenerative diseases linked to oxidative stress are becoming increasingly common, pushing researchers to explore natural compounds with antioxidant properties like flavonoids as potential alternatives for treatment. One promising source is Basella rubra L., or binahong leaves, which are traditionally used in herbal medicine and known to contain these beneficial compounds. This study set out to find out just how much flavonoid is in binahong leaf extract, and whether using different types of solvents during the extraction process would impact the results. The process began with a maceration technique using 70% ethanol to extract the active compounds. The extract was then separated into three fractions using a step-by-step method with n-hexane, ethyl acetate, and distilled water. To check the flavonoid content, the researchers applied a color-based test with FeCl₃ and also measured the levels using UV-Vis spectrophotometry at 417 nm. It turned out that all fractions contained flavonoids, but in varying amounts. The n-hexane fraction showed the highest level, followed by ethyl acetate, with distilled water yielding the lowest. These results highlight how the choice of solvent especially its polarity plays a key role in how effectively flavonoids are extracted from plants.